1999
DOI: 10.1002/(sici)1097-4660(199907)74:7<627::aid-jctb84>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Production of L‐lactic acid by Lactobacillus delbrueckii in chemostat culture using an ion exchange resins system

Abstract: L-Lactic acid production from beet molasses by Lactobacillus delbrueckii CECT 286 in a continuous fermenter-ion exchange resins system has been investigated and compared with that observed in a conventional chemostat. The principle of this method is to remove the lactate during the course of fermentation as it is formed by adsorption to an anion exchange resin (Amberlite IRA-420) in the carbonate form and to overcome its inhibitory effects on lactic acid bacteria by maintaining low lactate concentrations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…However, if an acidification resin such as Amberlite IR-120 was connected to the product recovery loop before the ion exchange resin to decrease the pH of the effluent, the acid loading onto the weak/strong base resin could be sufficiently increased. Studies done by Bishai et al [144] and Monteagudo & Aldavero [143], as shown in Table 1, have attempted this with strong and weak base resins, respectively, connected to lactate fermentation, resulting in increased product recovery and acid loading on the resin.…”
Section: Separation Using Ion Exchange Resinsmentioning
confidence: 99%
“…However, if an acidification resin such as Amberlite IR-120 was connected to the product recovery loop before the ion exchange resin to decrease the pH of the effluent, the acid loading onto the weak/strong base resin could be sufficiently increased. Studies done by Bishai et al [144] and Monteagudo & Aldavero [143], as shown in Table 1, have attempted this with strong and weak base resins, respectively, connected to lactate fermentation, resulting in increased product recovery and acid loading on the resin.…”
Section: Separation Using Ion Exchange Resinsmentioning
confidence: 99%
“…Therefore, only recovery by adsorption, extraction and pertraction are evaluated. Adsorptive based recovery involves adsorbents, which can range from (organic) resins to inorganic materials, like zeolites [35,36]. Only lactic acid adsorption on zeolite is considered in this paper, because the high stability of the zeolite adsorbent material is assumed to be favorable.…”
Section: Lactic Acidmentioning
confidence: 99%
“…solvent extraction (8)(9)(10), electrodialysis (11)(12)(13), adsorption onto activated carbon (14) or molecular sieves (3), and retention onto anion exchange resins (4,6,7,(15)(16)(17)(18), each with its own limitations. The toxicity of organic solvents for the cells is an important disadvantage of solvent extraction.…”
Section: Introductionmentioning
confidence: 99%